Perbandingan Kuat Tekan Paving Blok Berbahan Slag Nikel dengan Penambahan Berbagai Jenis Limbah Plastik - Husein, Laode Muhamad Syawal; Gunawan, Yuspian; Kadir, Abd (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
Indonesia's economic development is currently heavily dependent on the industrial sector  which  continues  to  experience  rapid  development.  One  of  the  growing industrial areas is the construction industry, especially infrastructure and property development  that  requires  materials  such  as  block  paving.  The  purpose  of  this research  is  to  find  out  the  comparison  of  strong  press  paving  blocks  with  the addition of nickel slag and plastic cacahan (PET, HDPE, LDPE and PP). This research uses conventional (manual) randomized methods. The results of this study showed that  the  influence  of  the  addition  of  nickel  slag  and  plastic  cacahan  in  the manufacture  of  paving  blocks  against  strong  press  can  be  concluded  that  the addition  of  nickel  and  plastic  slag  with  strong  characteristics  can  increase  the strength of paving block press. The highest average press strength values were in Sample C samples, with mixed variations (cement 25%, coarse aggregate 5%, slag 25%, fine aggregate 5% and HDPE plastic cacahan 40%). has a press force of 155 kg/cm2 with a quality of C based on SNI 03-0691-1996. The lowest press test results were  found  in  sample  E  (cement  25%,  coarse  aggregate  5%,  slag  25%,  fine aggregate 5% and plastic cacahan PP 40%) with a press test value of 87.5 kg/cm2 with a quality of D based on SNI 03-0691-1996. Keywords: Paving block, Plastic Type, Strong Press